Criminal Liability and Business Judgment Rule in Indonesia’s Sovereign Wealth Fund: The Case of BPI Danantara - Parameshwara; Ramlan; Khairul Riza (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This article examines the issue of criminal liability of corporate executives within the structure of Indonesia’s Sovereign Wealth Fund, particularly BPI Danantara, in relation to investment losses and anti-corruption enforcement. It highlights how regulatory inconsistencies and institutional overlap complicate legal accountability when public wealth is managed through a private corporate model. The purpose of this article is to critically analyze the legal construction of executive responsibility in BPI Danantara by examining the interplay between the Business Judgment Rule (BJR), the principle of public accountability, and the current limitations of corruption law enforcement in Indonesia. This study employs normative legal research using statutory, conceptual, historical, and case-based approaches. Legal sources include primary laws and constitutional court rulings, supported by secondary materials such as legal journals and authoritative commentaries. Analysis is conducted through juridisch denken (legal reasoning) to assess the consistency of norms. The findings of this study reveal that the current legal framework provides de jure protection to executives under the BJR, but in the absence of oversight and transparency, it may foster legal impunity. The classification of state-invested assets as private capital under BPI Danantara limits the scope of criminal liability, highlighting the urgent need for harmonization between corporate governance standards and anti-corruption legal norms in the context of sovereign wealth fund operations.